2002
DOI: 10.1097/00042560-200205010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Male Sexual Dysfunction Associated With Antiretroviral Therapy

Abstract: To determine whether treatment with protease inhibitors (PIs) is associated with male sexual dysfunction, we conducted a retrospective, cohort study of 254 adult male PI recipients who received care from the staff-model division of a large managed care organization in New England between 1993 and 1998. After a median of 5.0 years of observation, 80 incident cases of sexual dysfunction were observed. Relative to unexposed individuals, the rate of sexual dysfunction adjusted for confounding was most elevated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 18 publications
0
58
1
Order By: Relevance
“…Although HAART use has been linked to sexual functioning of HIV-positive men (e.g., Colson et al, 2002), the current study found that HIV-positive women described highly similar experiences of diminished sexual activity, a loss of sexual interest, and decreased feelings of attractiveness both before and after the advent of HAART. Relatedly, despite women often attributing various symptoms as side effects of antiviral medications, women described here did not attribute their diminished sexual interest or behavior to HAART.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although HAART use has been linked to sexual functioning of HIV-positive men (e.g., Colson et al, 2002), the current study found that HIV-positive women described highly similar experiences of diminished sexual activity, a loss of sexual interest, and decreased feelings of attractiveness both before and after the advent of HAART. Relatedly, despite women often attributing various symptoms as side effects of antiviral medications, women described here did not attribute their diminished sexual interest or behavior to HAART.…”
Section: Discussioncontrasting
confidence: 56%
“…Currently, little is known about whether the impact of being HIV-positive on sexuality has changed with the availability of HAART and the subsequent reconceptualization of HIV as a chronic disease rather than an acute life-threatening illness. HAART use has been linked to higher prevalence of sexual dysfunction among HIVinfected men (Collazos, Martinez, Mayo, & Ibarra, 2002;Colson et al, 2002;Lamba et al, 2004;Schrooten et al, 2001). Although the relationship between HAART and sexual functioning remains far less examined among HIV-positive women, the little research that has been done has found few differences.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have demonstrated an association with PIs (1,2,3,5) it is interesting that neither of the two groups that utilised the IIEF found a link with a particular class of medications (4,6).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…Deleted: There have been numerous reports of sexual dysfunction in HIV positive men with prevalence rates of up to 70% being described (1)(2)(3)(4)(5)(6) The primary objectives of this study therefore are to establish the prevalence of erectile dysfunction (EDF) and low sexual desire (LSD) in both ARV naïve and experienced HIV positive men attending HIV outpatient centres across Europe and to define the variables associated with sexual dysfunction. Due to the large number of variables that are potentially contributors to dysfunction a large amount of data relating to these variables was collected.…”
Section: Deleted: Sep_06mentioning
confidence: 99%
“…psychological factors including the depression brought forward by being HIV positive (Cove & Petrak, 2004) and exacerbated by the administration of antiretroviral therapy (ART, also known as HAART) (Colson et al, 2002) can contribute to the onset of erectile dysfunction. Previous research (Cove & Petrak, 2004) has indicated that up to 38% of HIV-positive gay men report experiencing erectile dysfunction, with an increase to 51% of men in the context of using a condom.…”
mentioning
confidence: 99%